2019
DOI: 10.1007/s11356-019-04678-1
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy and elemental analysis characterisation of microplastics in sediment of a freshwater urban river in Scotland, UK

Abstract: Understanding of the sources, fate, and impact of microplastics (MPs, < 5 mm) remains limited, particularly in freshwater environments, while limited comparability across available surveys hinders adequate monitoring and risk assessment of these contaminants. Here, the distribution of microscopic debris in an urban river close to the marine environment in the West of Scotland was investigated to assess concentration and distribution of primary and secondary MPs. Also, the efficiency of light and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(63 citation statements)
references
References 42 publications
2
60
0
1
Order By: Relevance
“…Scheurer and Bigalke (2018) found microplastics in 90% of the 29 floodplain soils analyzed across Switzerland, with concentrations ranging from 0 and 593 MPs kg −1 , correlated with the population of the catchment. Blair et al (2019) observed and 432 MPs kg −1 within two samples along the River Kelvin in Glasgow (UK), with fibers as the dominant shape (> 88%).…”
Section: Trapping Of Mps In the Têt River Bank Sedimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Scheurer and Bigalke (2018) found microplastics in 90% of the 29 floodplain soils analyzed across Switzerland, with concentrations ranging from 0 and 593 MPs kg −1 , correlated with the population of the catchment. Blair et al (2019) observed and 432 MPs kg −1 within two samples along the River Kelvin in Glasgow (UK), with fibers as the dominant shape (> 88%).…”
Section: Trapping Of Mps In the Têt River Bank Sedimentsmentioning
confidence: 97%
“…In Europe, only few studies investigated MPs in river shore sediments (Klein et al, 2015;Scheurer and Bigalke, 2018;Blair et al, 2019) using a similar methodology (surface samples, NaCl gravity separation, oxidation of natural debris and FTIR verification). Klein et al (2015) monitored shores along the Rhine and one of its major tributaries, the Main River, at a larger (~40 km) spatial scale than we did and with only a single sampling period.…”
Section: Trapping Of Mps In the Têt River Bank Sedimentsmentioning
confidence: 99%
“…SEM provides a highmagnification image of MPs, aiming for a structural false positive discrimination. When coupled with energy-dispersive spectroscopy (SEM-EDS), determination of the elemental composition is enabled (Blair et al, 2019). The lack of strong C signal in elemental spectra suggests a non-synthetic particle.…”
Section: Polymer Identificationmentioning
confidence: 99%
“…More broadly, they are distinguished as small plastic particles (primary source) and plastic debris (secondary source) (Frias, Otero, & Sobral, ; Moore, ). Primary microplastics comprise the plastic granules manufactured as product precursors for cosmetics, detergents, personal care products, and other industrial uses (Blair, Waldron, Phoenix, & Gauchotte‐Lindsay, ; Hidalgo‐Ruz, Gutow, Thompson, & Thiel, ). Secondary microplastics are produced by photolysis and hydraulic friction and exist as plastic debris, scales, fibers, and pellets of plastic waste from artificially discarded plastic waste such as beverage bottles, plastic bags, and fibers from synthetic textiles (Browne et al, ; Duis & Coors, ).…”
Section: Introductionmentioning
confidence: 99%